METHODOLOGIES FOR THE FORMATION OF COMMUNICATION SKILLS OF STUDENTS WITH HEARING IMPAIRMENT IN NATIVE LANGUAGE LESSONS - Isokjonova Dilfuzakhan (Web of Journals Publishing, 2025)
This article highlights the stages of formation of communication skills in students with hearing problems, the goals and objectives of each stage, the specificity of the practical work process.
Keywords: Methodology for working on words, methodology for working on vocabulary, methodology for forming sentence structure skills, methodology for working on sentence fragments, methodology for working on text, dictionary work.